Asymptomatic liver disease in haemophiliacs. Issue 8 (August 1975) - Mannucci, P M; Capitanio, A; Del Ninno, E; Colombo, M; Pareti, F; Ruggeri, Z M
Abstract : The incidence of jaundice and of abnormal liver function tests has been assessed in 91 multitransfused patients with severe haemophilia A and B. Tests of hepatocyte function were within the normal range in the majority of patients. On the contrary, tests of biliary cell function, liver cell damage, and bromsulphthalein retention gave high rates of abnormal values, which tended to increase with age. Hepatitis B surface antigen was present in 8% and the corresponding antibody in 66% of the cases; 18% had a history of jaundice. All patients were asymptomatic and only a minority showed clinical signs of liver involvement. These data suggest that in haemophilacs repeated and prolonged contact with the agent(s) responsible for post-transfusion hepatitis may cause chronic liver damage not associated with overt illness.